2015
DOI: 10.1016/j.ejmech.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation and preliminary mechanism study of novel benzothiazole derivatives bearing indole-based moiety as potent antitumor agents

Abstract: Through a structure-based molecular hybridization approach, a series of novel benzothiazole derivatives bearing indole-based moiety were designed, synthesized and screened for in vitro antitumor activity against four cancer cell lines (HT29, H460, A549 and MDA-MB-231). Most of them showed moderate to excellent activity against all the tested cell lines. Among them, compounds 20a-w with substituted benzyl-1H-indole moiety showed better selectivity against HT29 cancer cell line than other compounds. Compound 20d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The ligands containing indole moiety have shown potent and selective antitumor activity against various cells lines . In addition, metal complexes of such ligands have shown potential antimicrobial activity . Metal complexes with well‐defined coordination geometries and distinctive electrochemical properties can act as DNA binding agents .…”
Section: Introductionmentioning
confidence: 99%
“…The ligands containing indole moiety have shown potent and selective antitumor activity against various cells lines . In addition, metal complexes of such ligands have shown potential antimicrobial activity . Metal complexes with well‐defined coordination geometries and distinctive electrochemical properties can act as DNA binding agents .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the marked pharmacological activity of compound 73 might be ascribed to activation of procaspase-3 and cell cycle arrest. 81 A series of novel indolylquinones have been synthesized and evaluated for their antiproliferative activity against human MDA-MB-231 and MCF-7 BC cell lines. Among all these derivatives, 74 (IC 50 value ¼ 2.29 mg mL À1 for MCF-7 cells) and 75 (IC 50 value ¼ 3.99 mg mL À1 for MDA-MB-231 cells) displayed the most potent antiproliferative activity of the series and inhibited BC cells proliferation by triggering apoptotic cell death ( Table 5).…”
Section: The Indole or Isatin Functional Groupsmentioning
confidence: 99%
“…[15] PAC-1 and its derivatives induce apoptosis and are cytotoxic in cell culture to a diverse array of cancer cells, including cell lines derived from white blood cell cancers (lymphoma, [15, 4251] leukemia, [15, 24, 44, 4850, 5255] and multiple myeloma [24, 55]), diverse carcinomas (breast, [15, 44, 48, 49, 5254, 5659] renal, [15] adrenal, [15, 6062] colon, [15, 48, 55, 5759, 63] lung, [15, 48, 49, 5259, 6367] cervical, [44, 55] gastric, [48, 49, 55, 57, 58, 63] ovarian, [55] liver, [48, 49, 55] prostate, [48, 49] and gallbladder [48, 49]), and other solid tumor types (melanoma, [15, 44, 48, 49] osteosarcoma, [55] neuroblastoma, [15, 55, 57, 58] and glioblastoma [48, 49, 68]). Patient-derived samples from colon cancer [15], chronic lymphocytic leukemia [23], and multiple myeloma [24] are also sensitive to PAC-1 and derivatives, and a therapeutic effect has been demonstrated in multiple murine tumor models [15, 48, 49, 56, 65, 66, 69] and in pet dogs with cancer.…”
Section: Pac-1mentioning
confidence: 99%
“…This depletion of the labile zinc pool restores procaspase-3 enzymatic activity, allowing for cleavage of procaspase-3 to caspase-3 and the initiation of the execution pathway of apoptosis. [42] PAC-1 is now widely used as a tool compound for the induction of apoptosis [51, 59, 67, 68, 82, 83], and for the direct activation of procaspase-3 downstream of the mitochondria. [8487] In addition, multiple independent studies have confirmed the direct procaspase-3 activation mechanism, [48, 85, 88] for example in detailed studies with selective caspase inhibitors, [85] selective caspase substrates, [48] and in Bax/Bak double knockout cells.…”
Section: Pac-1mentioning
confidence: 99%